ANALISIS KESESUAIAN PERAIRAN TELUK LHOK RIGAH SEBAGAI LOKASI BUDIDAYA IKAN KERAPU BEBEK (Cromileptes altivelis) DENGAN SISTEM KERAMBA JARING APUNG (KJA) - Ika Kusumawati; Muhammad Arif Nasution; Riska Diana (Universitas Teuku Umar, 2017)
Humpback grouper requires suitable water quality for life whether physics, biology, or chemistry aspect. The purpose of this study is to determine the physical indicators, chemical parameters, and the appropriateness level of waters for potentially conducting fish farming activities of Humpback grouper by employing floating cage in waters of Bay Rigaih, Aceh Jaya District. Researcher conducted the study from August to September 2016 and employed survey approach. Determining the location of the sampling point is by using purposive sampling. The sampling coordinates recorded with the Global Positioning System (GPS). Based on data from research sampling, The results show mean value for each physical parameters such as: a). The depth is 9.5 m; b). the brightness is 3.7 m; c). water temperature is27,66 oc; d). The current speed is 20.25 cm/sec. Samples of some stations show mean values of chemical parameters such as: a). DO is 7.65 mg / l; b). pH is 7.59; c). salinity is 38.75 ppt. The High level of appropriatenessfor humpback grouper farming was shown at station 4 for every physical and chemical parameter, so itconcludesthat station 4 meet the criteria of quality waters for the development